(untitled) (Swiss Medical Weekly, 2011)
OBJECTIVE: To study the systemic production of inflammatory factors and activation of transcription factor nuclear factor kappa B (NF-κB) in response to different levels of intermittent hypoxia and time. METHODS: A total of 160 male Wistar rats were divided randomly into five groups. The first three groups were exposed to 5%, 7.5% and 10% intermittent hypoxia (referred to as IH-1, IH-2, and IH-3 respectively), the fourth group were subjected to 10% sustained hypoxia (abbreviated as SH), and the control group were exposed to normal oxygen (designated SC). At the second, fourth, sixth, and eighth week, eight rats in each group were sacrificed to collect serum. Enzyme-linked immunosorbent assay (ELISA) was used to detect the serum concentration of tumour necrosis factor alpha (TNF-α), interleukin-8 (IL-8), interleukin-6 (IL-6) and interleukin-10 (IL-10). Western blot was used to detect the protein levels of the phosphorylated NF-κB P65 in the nucleus of arterial endothelial cells. RESULTS: In all three IH groups serum levels of TNF-α, IL-8 and IL-6 showed consecutive increment from onset to the 6th week under intermittent hypoxia; the levels of TNF-α and IL-8 dropped slightly on the 8th week, whereas those of IL-6 continued to increase. The levels of IL-10 decreased and reached nadir at the 6th week of intermittent hypoxia treatment. The inflammatory response was the most pronounced in the 6th week, at which time the TNF-α, IL-8 and IL-6 levels in IH groups were significantly higher than in the SC and SH group (F = 30.04, 11.77, 18.589; p <0.05). IL-10 levels were significantly lower than the SC and SH group (F = 10.403, p <0.05). Levels of TNF-α and IL-8 in the IH-1 group were significantly higher than those in the IH-3 group (F = 1.20, 34.68; p= 0.049, 0.046). Protein levels of phosphorylated NF-κB P65 in endothelial cells collected from thoracic aorta in all three IH groups were significantly higher than those in SC and SH groups (F = 63.136, p =0.01). A close correlation was identified between NF-κB p65 phosphorylation and the levels of TNF-α, IL-8, IL-6 and IL-10 (p = 0.01). CONCLUSIONS:The inflammatory response, manifested by serum levels of inflammatory factors and nuclear accumulation of activated NF-κB P65, was more serious in the IH group than in the SH and control group, and was dependent on hypoxia levels. This reaction increased initially and then decreased, which indicates the presence of compensatory mechanisms and an adaptive response to such stressors in the body. Notably, the correlation of NFκB activation to production of inflammatory factors under intermittent hypoxia implies an important role of this transcription factor in inflammation-induced cardiovascular damage occurring during obstructive sleep apnoea (OSA), which has a typical breathing pattern of intermittent hypoxia.